Pengembangan Pembelajaran Pada Mata Pelajaran IPS Ekonomi Pada Siswa SMP Menggunakan Pendekatan Critical Pedagogy (The Development of Learning and Teaching Process of Social Subject of Economics In Junior High School Students Through Critical Pedagogy Approach) - Badrus Sholeh (Program Studi Pendidikan Ekonomi Universitas Pamulang, 2017)
The development of social science teaching and learning process in junior high school students using critical based approach plays a very important position in the development of education in Indonesia. This important position is in order to cultivate students into human participants who have good social intelligence and critical power. Therefore, the teachers who teach this subjects are required a breakthrough approach in teaching to stimulate students’ interest in learning economics at school. To stimulate interest in studying economics, the sets of learners should be brought closer to the social issues around their environtment which raised critical awareness in looking at the issues of socio-economic society. In this case study, the social subjects particularly at junior high school level should be based by using critical approach. By developing this learning and teaching activities, the learners was no longer dominated by any instruction and discourse thinking of the teachers. However, participants will construct their knowledge and educate themselves consciously and critically without the domination of anyone. This article wants to give an overview of the idea of critical pedagogy model of economic education in schools. This learning method is able to improve students ability in being private citizens both critically and responsibly.Keywords: Learning Process Development, Social Subject of Economics, Junior high school students, Critical Pedagogy.